What Drives Consumer Purchase Intention on Products Offered by E- Commerce During the Covid-19 Pandemic? An Empirical Study at Tokopedia - Parlin Purba; Ari Setiyaningrum (Jurnal Manajemen Indonesia, 2022)
The main purpose of this research is to test a model to prove whether perceived usefulness, perceived ease of use, cost saving and time saving affect purchase intention directly or indirectly through perceived customer value. The research model was tested in e-commerce contexts at Tokopedia during the Covid-19 pandemic. Primary data were collected by distributing questionnaires to 313 people who had visited Tokopedia website or application but have never made a purchase. The purposive sampling technique is used in this research. Data analyzed using the partial least square method with SmartPLS. The findings indicated that perceived ease of use affects purchase intention, whereas perceived usefulness, cost saving, and time saving do not affect purchase intention. The results of the indirect effect prove perceived customer value mediates the effect of cost saving and time saving on purchase intention, while perceived customer value does not mediate the effect of perceived usefulness and perceived ease of use on purchase intention. The research findings also show that cost saving and time saving affect perceived customer value, whereas perceived usefulness and perceived ease of use do not affect perceived customer value, and perceived customer value affects purchase intention. Keywords— perceived usefulness; perceived ease of use; cost saving; time saving; perceived customer value; purchase intention.